Genarchella parva Travassos, Artigas & Pereira, 1928 (Digenea: Derogenidae) in fish from two environments in southern Brazil: morphology and comments on host’s checklist - Gallas, Moisés (2023)
Genarchella parva Travassos, Artigas & Pereira, 1928 has been reported mainly in Characidae hosts. The morphology of this species has been known based on specimens collected mainly by Travassos and researchers (20s and 60s decades) and also from specimens in Argentina. The goal of this study was to describe the morphology of G. parva, provide the parameters of the infections from different fish species and discuss the host’s checklist from Brazil. Specimens of G. parva were collected from species of Astyanax Baird & Girard, 1854 and Psalidodon Eigenmann, 1911 in Jacuí Delta (north of the Lake Guaíba, in the municipality of Porto Alegre) and Lagoon Itapeva (municipality of Terra de Areia), extreme south of Brazil. The localization of the genital pore of G. parva and Genarchella fragilis Lunaschi, 1990 was compared and discussed. The prevalence of G. parva was higher in Psalidodon aff. fasciatus (Cuvier, 1819) (12.9%) from Itapeva Lagoon and Astyanax henseli Melo & Buckup, 2006 (11.43%) from Jacuí Delta than other species examined. A host’s checklist of G. parva in Brazil is provided and two previous reports are discussed. This study is the first report of G. parva in A. henseli and A. lacustris from southern Brazil, while Itapeva Lagoon is considered a new locality record for G. parva.